2013
DOI: 10.5194/cp-9-2195-2013
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble organic carbon in snow and ice deposited at Alpine, Greenland, and Antarctic sites: a critical review of available data and their atmospheric relevance

Abstract: While it is now recognized that organic matter dominates the present-day atmospheric aerosol load over continents, its sources remain poorly known. The studies of organic species or organic fractions trapped in ice cores may help to overcome this lack of knowledge. Available data on the dissolved (or total) organic carbon (DOC or TOC) content of snow and ice often appear largely inconsistent, and, until now, no critical review has been conducted to understand the causes of these inconsistencies. To draw a more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 74 publications
(86 reference statements)
2
43
1
Order By: Relevance
“…As discussed by Grannas et al (2007), the relevance of this secondary production was supported even for Antarctica by the significant presence of dissolved fulvic acid reported for Antarctic snow (26-46 ppb C) by Calace et al (2005). However, the previously assumed ubiquitous presence of organics in polar snow that is needed to reduce NO 2 into HONO was recently reviewed by Legrand et al (2013), who found that organics (and humic acids) are far less abundant in Antarctica compared to Greenland or midlatitude glaciers like the Alps. For instance, the typical dissolved organic content of summer surface snow is only 10-27 ppb C at DC (Legrand et al, 2013) as opposed to 110 ± 45 ppb C at Summit and 300 ppb C in the Alps.…”
Section: Hono Observations At Concordiamentioning
confidence: 96%
See 2 more Smart Citations
“…As discussed by Grannas et al (2007), the relevance of this secondary production was supported even for Antarctica by the significant presence of dissolved fulvic acid reported for Antarctic snow (26-46 ppb C) by Calace et al (2005). However, the previously assumed ubiquitous presence of organics in polar snow that is needed to reduce NO 2 into HONO was recently reviewed by Legrand et al (2013), who found that organics (and humic acids) are far less abundant in Antarctica compared to Greenland or midlatitude glaciers like the Alps. For instance, the typical dissolved organic content of summer surface snow is only 10-27 ppb C at DC (Legrand et al, 2013) as opposed to 110 ± 45 ppb C at Summit and 300 ppb C in the Alps.…”
Section: Hono Observations At Concordiamentioning
confidence: 96%
“…However, the previously assumed ubiquitous presence of organics in polar snow that is needed to reduce NO 2 into HONO was recently reviewed by Legrand et al (2013), who found that organics (and humic acids) are far less abundant in Antarctica compared to Greenland or midlatitude glaciers like the Alps. For instance, the typical dissolved organic content of summer surface snow is only 10-27 ppb C at DC (Legrand et al, 2013) as opposed to 110 ± 45 ppb C at Summit and 300 ppb C in the Alps. Furthermore, recent HULIS (humiclike substance) measurements of surface snows collected at DC do not confirm the previously observed abundance (2 instead of 26-46 ppb C).…”
Section: Hono Observations At Concordiamentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonaceous matter contained in glaciers and ice sheets includes WSOC and insoluble particulate carbon (IPC) (Legrand et al, 2013a;Li et al, 2016a). The characteristics of WSOC can reflect the quality of atmospheric environment so that it was used as a proxy to study past anthropogenic influence on the atmospheric load and composition of organic compounds/matter at the glacial region ( Legrand et al, 2013a, b ).…”
Section: Introductionmentioning
confidence: 99%
“…Water soluble organic carbon (WSOC) constitutes a major fraction (20-80%) of the organic carbon in glacierized regions, and has important influences on the energy budget and radiative forcing of glaciers (Ram et al, 2010;Khare et al, 2011;Pavuluri et al, 2011;Legrand et al, 2013a;Kirillova et al, 2014a,b;Yan et al, 2016). Mountain glaciers and ice sheets cover 11% of the land surface on Earth and store 6 petagrams of organic carbon (OC), the majority of which is WSOC (Hood et al, 2015;Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%